A new biological marker in inflammatory bowel disease: Pentraxin 3 - Kalyon, Semih; Gökden, Yasemin; Oyman, Fırat (Journal of Surgery and Medicine, 2020)
Aim: Pentraxin 3 is a molecule that is known to show inflammation, however few studies with contradictory results have been conducted in current literature in Inflammatory Bowel Disease patients regarding PTX3. We aimed to investigate whether PTX3 can be used in the discrimination of Crohn’s disese and Ulcerative colitis patients and whether there is a correlation of PTX3 with disease activity, involved intestinal segments and their length. Method: Ethical committee approval was obtained for this a prospective, single-centered, single-blind study. IBD patients who were older than 18 years old, without pregnancy, malignancy, acute/chronic infections or inflammatory diseases were included. Healthy volunteers were included in study as a control group. PTX3 levels were measured in the blood. Shapiro-Wilk, Mann-Whitney U, Kruskal Wallis, Bonferroni-Dunn, Spearman tests were used with NCSS 2007 program. Results: The median age of the 56 male and 42 female participants was 37 years (25 CD, 43 UK and 30 controls). In the UK group, PTX3, which did not have relationship with the Trulove Witts score or the Mayo score; was a statistically significant higher in patients with pancolitis. There was no relationship between PTX3 levels and involvement, behavior pattern, CDAI scores and activity of the disease in CD group. Conclusion:PTX3 is not an appropriate biomarker for monitoring the activation of İBD and it can’t distinguish two subtypes from eachother. PTX3 is insufficient to indicate both the behavior pattern and the location of involvement in CD patients. Only, until the control endoscopy times of the patients with UK, it can be monitored whether the disease affects the entire colon by following the PTX3 levels in the interim period.